Analysis of library space comfort in supporting student well-being at Universitas Muhammadiyah Sumatera Utara - Sitepu, Yuni Larasanti Nurhasanah br; Syam, Abdi Mubarak (Faculty of Communication, Padjadjaran University, 2026)
Background: Modern academic libraries no longer function solely as providers of academic information, but also as spaces that support students' comfort and well-being. This study analyses the spatial comfort of the Library of Universitas Muhammadiyah Sumatera Utara and its relationship with student well-being.Purpose: The aim of this research is to evaluate the role of facilities and a sense of safety in creating spatial comfort, as well as to identify the challenges encountered.Methods: This study employed a qualitative case study approach to analyse library space comfort and its relationship with students' well-being at the Universitas Muhammadiyah Sumatera Utara Library. Data were collected through in-depth interviews, observation, and documentation involving librarians and students who actively utilise the UMSU library. The analysis was conducted through data reduction, data display, and conclusion drawing, using Environmental Psychology theory and the Learning Commons concept as analytical lenses.Results: The results indicate that physical aspects (lighting, noise, and layout) and psychological aspects (sense of safety) are the main determinants of spatial comfort, which contribute to reducing students' academic stress. The findings also show that comfortable library spaces improve students' concentration, emotional stability, and learning experiences.Conclusions: In conclusion, libraries are no longer perceived merely as places for studying and discussion, but also as